Mutagenic Impact and Evolutionary Influence of Chemoradiotherapy in Hematologic Malignancies - Diamond, Benjamin; Chahar, Dhanvantri; Jain, Michael D; Poos, Alexandra M; Durante, Michael A; Ziccheddu, Bachisio; Kaddoura, Marcella; Papadimitriou, Marios; Maclachlan, Kylee H; Jelinek, Tomas; Davies, Faith E; Figura, Nicholas B; et al. (Blood cancer discovery, 2025)
UNLABELLED: Ionizing radiotherapy (RT) is a widely used treatment strategy for malignancies. In solid tumors, RT-induced double-strand breaks lead to the accumulation of insertion-deletions (indels; ID), and their repair by nonhomologous end joining has been linked to the ID8 mutational signature in surviving cells. However, the extent of RT-induced mutagenesis in hematologic malignancies and its impact on their mutational profiles and interplay with commonly used chemotherapies has not yet been explored. In this study, we interrogated 580 whole-genome sequence (WGS) samples from patients with large B-cell lymphoma, multiple myeloma, and myeloid neoplasms and identified ID8 only in relapsed disease. Yet ID8 was detected after exposure to both RT and mutagenic chemotherapy (i.e., platinum and melphalan). Using WGS of single-cell colonies derived from treated lymphoma cells, we revealed a dose-response relationship between RT and platinum and ID8. Finally, using ID8 as a genomic barcode, we demonstrate that a single RT-surviving cell may seed distant relapse. SIGNIFICANCE: RT and the ID8 indel signature are related, but their genomic impact on hematologic malignancies is unclear. Leveraging WGS, we linked ID8 to both RT and mutagenic chemotherapy and validated that platinum can induce ID8. We used ID8 as a genomic barcode to reveal that RT-resistant cells may seed systemic relapse.
Keywords: Chemoradiotherapy; lidé; mutageneze; chemoradioterapie; Hematologic Neoplasms; Whole Genome Sequencing; sekvenování celého genomu; mutace; Humans; Male; Mutagenesis; mužské pohlaví; Mutation; hematologické nádory; ženské pohlaví; Female